We can simplify using the exponent rules:
74 × 7 × 713 × 7^(-20)
First, let's simplify the multiplication: 74 × 7 = 518.
Now, let's simplify the exponent rule: 7^(-20) = 1 / 7^20.
Therefore, the simplified expression is 518 × 713 × (1 / 7^20).
Simplify using Exponent Rules: 74×7×713×7−20 (1 point)
9 answers
Simplify using Exponent Rules: 74×7×713×7−20 (1 point)
28^-2
1/7^2
1/7^3
1/7^-2
28^-2
1/7^2
1/7^3
1/7^-2
To simplify 28^(-2), which means "28 raised to the power of -2," we can apply the exponent rule that states a negative exponent is equal to 1 divided by the number raised to the positive exponent:
28^(-2) = 1 / 28^2
Similarly, for 7^(-2) and 7^(-3), we have:
7^(-2) = 1 / 7^2
and
7^(-3) = 1 / 7^3
However, the last expression, 1/7^(-2), needs to be rewritten using exponent rules. A negative exponent in the denominator indicates that the base should move to the numerator.
1/7^(-2) = 7^2
So the simplified expressions are:
28^(-2) = 1 / 28^2
7^(-2) = 1 / 7^2
7^(-3) = 1 / 7^3
1/7^(-2) = 7^2
28^(-2) = 1 / 28^2
Similarly, for 7^(-2) and 7^(-3), we have:
7^(-2) = 1 / 7^2
and
7^(-3) = 1 / 7^3
However, the last expression, 1/7^(-2), needs to be rewritten using exponent rules. A negative exponent in the denominator indicates that the base should move to the numerator.
1/7^(-2) = 7^2
So the simplified expressions are:
28^(-2) = 1 / 28^2
7^(-2) = 1 / 7^2
7^(-3) = 1 / 7^3
1/7^(-2) = 7^2
Simplify using Exponent Rules: 7^4×7×7^13×7^−20 (1 point)
28^-2
1/7^2
1/7^3
1/7^-2
28^-2
1/7^2
1/7^3
1/7^-2
To simplify 7^4 × 7 × 7^13 × 7^(-20), we can apply the exponent rule that states when multiplying with the same base, we add the exponents:
7^4 × 7 × 7^13 × 7^(-20) = 7^(4 + 1 + 13 + (-20))
Now, we can simplify the exponent:
7^(4 + 1 + 13 + (-20)) = 7^(-2)
So, the simplified expression is: 7^(-2)
Therefore, the correct answer is "28^-2".
7^4 × 7 × 7^13 × 7^(-20) = 7^(4 + 1 + 13 + (-20))
Now, we can simplify the exponent:
7^(4 + 1 + 13 + (-20)) = 7^(-2)
So, the simplified expression is: 7^(-2)
Therefore, the correct answer is "28^-2".
Fully simplify using Exponent Rules: (5^8/5^6)^2
1^4
5^2
25^4
5^4
1^4
5^2
25^4
5^4
To simplify the expression (5^8/5^6)^2 using the exponent rules, we can apply the rule that when dividing with the same base, we subtract the exponents:
(5^8/5^6)^2 = 5^(8-6)^2
Simplifying the exponent:
5^(8-6)^2 = 5^2^2
Simplifying further:
5^2^2 = 5^4
So, the fully simplified expression is 5^4.
Therefore, the correct answer is 5^4.
(5^8/5^6)^2 = 5^(8-6)^2
Simplifying the exponent:
5^(8-6)^2 = 5^2^2
Simplifying further:
5^2^2 = 5^4
So, the fully simplified expression is 5^4.
Therefore, the correct answer is 5^4.
Simplify using the Exponent Rules: (Your answer can have only positive exponents) (x^3) (x^-6)/(x^2)^5
x^7
1/x^28
1/x^13
x^8
x^7
1/x^28
1/x^13
x^8
To simplify the expression (x^3) (x^-6)/(x^2)^5 using the exponent rules, we can apply the rules for multiplying and dividing exponents with the same base:
(x^3) (x^-6)/(x^2)^5 = x^(3 + (-6) - 5 * 2)
Simplifying the exponents:
x^(3 + (-6) - 5 * 2) = x^(3 - 6 - 10)
Further simplifying:
x^(3 - 6 - 10) = x^(-13)
Since we need the answer to have only positive exponents, we can rewrite x^(-13) as 1/x^13.
So, the simplified expression is 1/x^13.
Therefore, the correct answer is 1/x^13.
(x^3) (x^-6)/(x^2)^5 = x^(3 + (-6) - 5 * 2)
Simplifying the exponents:
x^(3 + (-6) - 5 * 2) = x^(3 - 6 - 10)
Further simplifying:
x^(3 - 6 - 10) = x^(-13)
Since we need the answer to have only positive exponents, we can rewrite x^(-13) as 1/x^13.
So, the simplified expression is 1/x^13.
Therefore, the correct answer is 1/x^13.